A Framework for Incorporating the Impact of Water Quality on Water Supply Stress: An Example from Louisiana, USA. (26th October 2017) - Borrok, David M.; Chen, Jian; Eldardiry, Hisham; Habib, Emad
Abstract: Water of poor quality can directly impact the budget of water available for key user groups. Despite this importance, methods for quantifying the impact of water quality on water availability remain elusive. Here, we develop a new framework for incorporating the impact of water quality on water supply by modifying the Water Supply Stress Index (WaSSI). We demonstrate the usefulness of the framework by investigating the impact of high salinity waters on the availability of irrigation water for agriculture in Louisiana. The WaSSI was deconstructed into sectoral components such that the total available water supply could be reduced for a particular demand sector (agricultural irrigation in this example) based on available water quality information. The results for Louisiana highlight substantial impacts on water supply stress for farmers attributable to the landward encroachment of saline surface water and groundwater near the coast. Areas of high salinity near the coast also increased the competition for freshwater resources among the industrial, municipal, and agricultural demand sectors in the vicinities of the municipal areas of Lake Charles, Lafayette, and Baton Rouge, Louisiana. The framework developed here is easily adaptable for other water quality concerns and for other demand sectors, and as such can serve as a useful tool for water managers.